Experiments with air - Tocci, Salvatore; Rasch, Patricia (New York Children's Press, 2003)
Explores the properties of air and air pressure through ten simple experiments using everyday objects
Includes bibliographical references (p. 44) and index
Hurg
5
Keywords: Air -- Experiments; Air